Catabolic pathway of arginine in Anabaena involves a novel bifunctional enzyme that produces proline from arginine. Issue 4 (25th February 2019) - Burnat, Mireia; Picossi, Silvia; Valladares, Ana; Herrero, Antonia; Flores, Enrique
Summary: Arginine participates widely in metabolic processes. The heterocyst‐forming cyanobacterium Anabaena catabolizes arginine to produce proline and glutamate, with concomitant release of ammonium, as major products. Analysis of mutant Anabaena strains showed that this catabolic pathway is the product of two genes, agrE ( alr4995 ) and putA ( alr0540 ). The predicted PutA protein is a conventional, bifunctional proline oxidase that produces glutamate from proline. In contrast, AgrE is a hitherto unrecognized enzyme that contains both an N‐terminal α/β propeller domain and a unique C‐terminal domain of previously unidentified function. In vitro analysis of the proteins expressed in Escherichia coli or Anabaena showed arginine dihydrolase activity of the N‐terminal domain and ornithine cyclodeaminase activity of the C‐terminal domain, overall producing proline from arginine. In the diazotrophic filaments of Anabaena, β‐aspartyl‐arginine dipeptide is transferred from the heterocysts to the vegetative cells, where it is cleaved producing aspartate and arginine. Both agrE and putA were found to be expressed at higher levels in vegetative cells than in heterocysts, implying that arginine is catabolized by the AgrE ‐ PutA pathway mainly in the vegetative cells. Expression in Anabaena of a homolog of the C‐terminal domain of AgrE obtained from Methanococcus maripaludis enabled us to identify an archaeal ornithine cyclodeaminase. Abstract : The heterocyst‐forming cyanobacterium Anabaena catabolizes [14C]arginine generating proline and glutamate as major products, as shown by thin layer chromatography. This pathway involves only two enzymes, AgrE and PutA. AgrE is a novel bifunctional enzyme that produces proline from arginine with ornithine as an intermediate. An enzyme homologous to the second domain of AgrE that catalyzes the cyclodeamination of ornithine is also found in Methanococcus.